Assessment of Police Integrity and Corruption: Causes, Efficacy and Different Prevention Strategies - (:unkn) unknown (My University, 2023)
This chapter aims to identify key issues in police integrity and corruption, with a specific emphasis on the causes of corruption and the efficacy of different prevention strategies. The police are the initial faces of law enforcement and commence the criminal justice process and thus hold significant responsibility for functioning law and order. As key representatives of the state, the integrity of the police in all societies is pivotal to retain public trust in the rule of law and the preservation of internal security. The article focuses on the origins and effects of police corruption, including the connections between integrity (and breaches in it) and the growth of corruption, as well as methods for teaching personnel about organizational principles and integrity. This research does not seek to evaluate the type or degree of police corruption that exists in South Africa at the moment. Three crucial, interconnected issues must be the focus of initiatives to improve police oversight and accountability. Firstly, where policing has been militarized and may be undemocratic and authoritarian, efforts must be made to enhance civilian control over the police. Secondly, it is necessary to increase public confidence in the police by upgrading levels of police service delivery as well as by investigating and acting in cases of police misconduct. Thirdly, reducing corruption within the police is crucial. Finally, the article suggests that a holistic anticorruption strategy, rather than a linear one, has the potential to raise awareness, increase pay to deter petty forms of corruption, install independent anticorruption agencies, and periodically rotate police officers to increase police integrity and loyalty for the host country. It is recommended that these multifaceted prevention strategies are needed within a police force that is faced with a violently divided society to reaffirm public support and deter support for armed anti-governmental oppositional g
Keywords: African Research